An Overview of Southern African PGM Smelting - R. T. Jones (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
The largest known platinum group metal (PGM) deposit in the world is the Bushveld Complex in South Africa, with the Great Dyke in Zimbabwe also being one of the biggest. It is therefore not surprising that the majority (just over 5 million troy ounces or 156 metric tons per annum) of the world's platinum is produced in Southern Africa. Primary smelting of ore concentrates is carried out in that region by five companies, namely Anglo Platinum, Impala Platinum, Lonmin Platinum, Northam Platinum, all of South Africa, and Makwiro Platinum in Zimbabwe. The only other primary smelter of platinum group metals is Stillwater Mining of Montana, USA, although very significant quantities of PGMs are produced as co-products by Norilsk Nickel of Russia. Smaller (but still significant) quantities of PGMs are produced by Falconbridge and Inco of Canada, also as co-products from nickel sulphide smelting. There are many similarities between PGM smelting and nickel sulphide smelting, and the range of technologies in use includes six-in-line rectangular electric furnaces, three-electrode circular AC furnaces, Peirce-Smith converters, and Anglo's ACP (based on Ausmelt technology). PGMs are also recovered from residue materials using DC arc furnace technology.